Birokrasi pemerintah Indonesia di era Reformasi - Thoha, Miftah (Rawamangun, Jakarta : Kencana, 2008)
Development of bureaucracy reform in Indonesia.
Includes bibliographical references (p. [129]-136) and index.
Keywords: Civil service reform -- Indonesia; Bureaucracy -- Indonesia